Tinjauan Hukum Islam Terhadap Pembiayaan Murabahah dan Mudharabah Bagi Pelaku Usaha Kecil Menengah (UKM) (Studi di BMT Wihdatul Ummah Desa Plaosan Kabupaten Magetan) - fathul mujaddidi arum (Journal of Islamic Business Law, 2018)
BMT (Baitul Mal Wat Tamwil) that consist of two terms is baitul mal and baitul tamwil, baitul mal disposer on the businesses collection and distribution of fund that no-profit such as zakat, infaq and shadaqah. While baitul tamwil as a business collection and distribution of commerce fund.The objective of this research is to know the practice of murabahah and mudharabah at baitul mal wat tamwil (BMT) Wihdatul Ummah the Actor of Small and Medium Enterprises under the Perspective of Islamic Law. The finding of this research can be concluded that the practice of murabahah and mudharabah financing that used by baitul mal wat tamwil (BMT) Wihdatul Ummah Magetan Regency under the perspective of Islamic law. While, in the mudharabah financing a problem in thecapitalorthe granting ofloans tothe customer of UKM (small and medium enterprises),becausehave not beenable to give lenda lot, butcan onlyprovideventure capitalloanfor aboutup to 20 million, theCustomerpickintermsof contractMudahrabah.